Comparative Performance of Wastewater Treatment with Intermittent Palm Kernel Shells (PKS) and Slow Sand Filtration (SSF) - Ganiyu A. SODAMADE; Odum L. ODUM; Ezechiel O. LONGE (UNIABUJA Journal of Engineering and Technology (UJET), 2025)
The impact of effluents from an institutional wastewater treatment plant is of great concern due to high concentration of effluent pollutants than the recommended standard limits. Ability of using a locally available filter material around the point of generation and making use of low-cost technology is highly desirable. The study focused on comparing the performance of laboratory scale intermittent filtration system using granulated Palm Kernel Shell (gPKS) as filter medium with an existing slow sand filtration (SSF) system. The gPKS was collected from Arigbajo Community in Ogun State, Nigeria. The filter depth and loading of the existing SSF of 0.65 m and 0.135 L/min respectively was adopted for the gPKS column. The 5-day Biochemical Oxygen Demand (BOD5) removal efficiency for the gPKS and SSF were 52.98 and 81.11% respectively. There was a slight increase (7.62 and 0.92%) in the nitrate of the effluents from both the gPKS and SSF also a slight increase of 0.5 and 0.42 mg/l for gPKS and SSF respectively were witnessed for the dissolved oxygen. Total bacteria removal in both systems was 99.9%. It can be concluded that gPKS can serve as a filter medium in intermittent sand filtration for a tertiary wastewater treatment to replace SS.